2019
DOI: 10.3390/diagnostics9030102
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative MRI Parameters Predict Urinary Continence after Robot-Assisted Laparoscopic Prostatectomy in Prostatic Cancer Patients

Abstract: We aimed to investigate whether preoperative MRI findings could predict the bladder neck location on postoperative cystography and recovery of urinary incontinence after robot-assisted laparoscopic radical prostatectomy (RALP). We retrospectively reviewed 270 consecutive patients who had complete preoperative data, including MRI, and underwent postoperative observation for more than three months. Preoperative MRI parameters consisted of the membranous urethral length (MUL) and pubic symphysis-prostate apex len… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 15 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…Based on previous literature, among the image-based predictors for PPI, including a intravesical protrusion, the membranous urethral length (MUL), the prostatic volume, and periurethral fibrosis [ 25 , 26 , 27 , 28 ], MUL on the preoperative MRI is one of the most discussed [ 14 ]. More than 20 articles have discussed the predictive value of MUL for PPI, with a significant correlation clearly identified between a longer length pre-surgery and continence after surgery, suggesting that MUL could be an independent predictor for early recovery from PPI [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on previous literature, among the image-based predictors for PPI, including a intravesical protrusion, the membranous urethral length (MUL), the prostatic volume, and periurethral fibrosis [ 25 , 26 , 27 , 28 ], MUL on the preoperative MRI is one of the most discussed [ 14 ]. More than 20 articles have discussed the predictive value of MUL for PPI, with a significant correlation clearly identified between a longer length pre-surgery and continence after surgery, suggesting that MUL could be an independent predictor for early recovery from PPI [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several authors showed a correlation between increasing MUL and preservation of urinary continence after prostatectomy and, consequently, support MUL as a predictor factor for recovery of urinary continence. [27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43] Indeed, several studies attempted to predict the probability of post-RP continence by using preoperative MRI measurements of MUL, with the largest retrospective study analyzing 602 men and showing a significant association between MUL and continence outcomes at 12 months post-RARP. 28 Some authors additionally evaluated the difference in MRI-measured MUL before and after surgery, and the percentage change of MUL (calculated as [(preoperative MUL À postoperative MUL) 9 100] / preoperative MUL), showing these to significantly correlate with urinary continence after RP.…”
Section: Mrimentioning
confidence: 99%
“…In addition to the parameters reported above, Fuki et al 31 assessed both prostate volume and pubic symphysis-PAL, showing PAL to be a predictive factor of PPUI at 3 months after RARP. Paparel et al also showed that a high degree of periurethral fibrosis in the postoperative phase correlated with worsening continence.…”
Section: Mrimentioning
confidence: 99%
“…The sagittal dynamic MRIs were acquired at resting and during the abdominal pressure phase using a fast spin-echo sequence with the following parameters: repetition time/echo time: 1,500-3,716 ms/85-104 ms, ap angle: 90°, slice thickness: 6 mm; eld of view: 300 mm, and imaging matrix: 224-352 × 156-224. Figure 1 illustrates the measurements of the following: distance from the distal end of the membranous urethra to the pelvic outlet (DMU-PO) 11,12 , distance from the bladder attachment to the pubic symphysis (BA-PS), the MUL, prostate length (PL), and distance from the pubic symphysis to prostate apex length (PAL) 13 , and the length from the bladder neck to the pubic symphysis (BN-PS) 8 .…”
Section: Surgical Techniquementioning
confidence: 99%